JNI Fault Tolerance Using Java ProcessBuilder - Kwang Hooi, Yew (2011)
An application can be crippled by the memory leakage of one of its components. Unfortunately, access to the source code of a referenced component, for rectification, is often not feasible. This paper presents our experience of using multi-processing as a strategy to contain the problem. We demonstrate the use of Java ProcessBuilder to protect applications from unstable native code accessed via the Java Native Interface. The technique discussed can help in designing applications that provide better fault tolerance without costing much memory utilization.